Associação de aditivos na terminação intensiva de bovinos de corte em pastagem tropical : caracterização da carcaça e qualidade da carne - Groth, Andressa (2023)
In order to obtain a quality and uniform product, there is a need to know the factors that influence the characteristics of meat quality. In this context, the use of lasalocid alone or associated with other additives was evaluated on changes in carcass characteristics and meat quality of beef cattle undergoing intensive finishing on tropical pasture. To evaluate carcass composition, 225 non-castrated male Nelore animals were used, with an average initial age of 18 to 20 months and an average body weight of ± 430 kg. The experiment was conducted in a completely randomized design, with 5 treatments and 3 replications, with 15 paddocks with 15 animals each. The treatments consisted of varying additives in each concentrate: L (Lasalocida); L+AC (Lasalocida + Actigen®); L+ADV (Lasalocida + ADV Fortuna LM: Sacharomyces cerevesiae yeast mix 3.2 x 10E9 CFU/kg); L+ PRO (Lasalocida + Probios Precise®); L+ LI (Lasalocida + LithoNutri®). For physical characteristics and meat quality, 45 cattle were used, 3 animals from each paddock, totaling 9 animals per treatment. No difference (P< 0.05) was observed for the evaluation parameters, physical and chemical composition of the carcass, except for hot carcass yield, which showed better yields in the L+AC, L+ADV and L+ PRO treatments, and an average of 56.95% between treatments. Although there was no significant difference, the crude protein value was higher than that found in the literature, with an average of 26.28%. The use of ultrasound to evaluate carcass composition proved to be a viable tool, presenting an average difference between observed and estimated data of -0.20cm² for Rib Eye Area (AOL) and -0.08mm for Subcutaneous Fat Thickness (EGS). The use of lasalocid alone or in combination with different additives in the diet of Nelore cattle finished intensively on pasture does not alter the physical and chemical composition of the carcass, as well as the quality of the meat. Therefore, the use of isolated Lasalocida is the most recommended as it has a lower cost, obtaining the same results.